Treatment of hallux valgus in adults: A comparison study between the closing wedge and scarf technique of the first metatarsal bone osteotomy - Alali, Mohanad Ismail; Mohamed, Ezzat Shafiq; Saad, Maan Mohamed (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to evaluate the results of surgical treatments of hallux valgus by a scarf or closing wedge osteotomy of the first metatarsal. In addition to, detection complications resulting from the surgery. Patients and Methods: Descriptive comparative study was conducted for the period of one year (June2020 – June2021) at Tishreen University Hospital in Lattakia- Syria. The study included two groups of patients that were compared: group1 consisted of 19 patients (57.6%) who underwent closing wedge osteotomy, whereas group 2 consisted of 14 patients (42.4%) who underwent scarf procedure. Results: The mean hallux valgus angle (HVA) decreased from (31.43 º ±3.1) preoperatively to (9.15 º ±0.1) at postoperative in closing wedge group (group. 1), and from (29.45 º ±2.7) preoperatively to (10.10 º ±3.7) at postoperative in scarf group (group. 2), p:0.0001. The Foot and Ankle Disability Index (FADI) score increased significantly in the two groups during follow- up periods. Complications developed in the two groups, more frequently in the scarf group which included: wound healing after 8 weeks (35.7% vs 22.2%), operation site infection (21.4) % vs (11.1%), sudeck's disease (14.3% vs 5.6%), impaired wound healing (14.3% vs 5.6%) and recurrence of hallux valgus (7.1% vs 5.6%), without any case of the non- healing wound in the two groups. Satisfaction of the patients was complete in 84.8%, moderate in 9.1%, and 6.1% of the patients were unsatisfied. Conclusion: The current study demonstrated favorable results in correction deformity with two techniques, with fewer complications in closing wedge compared with the scarf method.
Keywords: Hallux valgus; scarf; closing wedge